INTENSI BERWIRAUSAHA PADA GENERASI MILENIAL: PERSPEKTIF KEPRIBADIAN - Kurjono Kurjono; Yola Yolanda (Jurnal Pendidikan Ilmu Sosial, 2022)
The challenge of finding a job for college graduates are getting tighter due to the number of jobs with an unbalanced workforce. One solution to overcome this problem is to become an entrepreneur. This study aims to look at the influence of locus of control, tendency to take risks, self-confidence, need for achievement, tolerance for ambiguity, and innovation, on entrepreneurial intentions. The grand theory used is the Planned Behavior Theory from Ajzen (1991). The research method used is the explanatory survey method. The study population was 19,919 students with a sample size of 366 respondents. The research sample was taken from the UPI student population. Collecting data using a questionnaire that has been tested for the level of validity and reliability. The data processing technique used descriptive analysis and regression analysis. The results showed that locus of control, propensity to take risks, selfconfidence, need for achievement, tolerance for ambiguity, and innovation had a positive and significant effect on entrepreneurial intentions. Innovation as the most dominant factor influencing entrepreneurship intention. There is no difference in entrepreneurship intention from the aspect of gender. It is recommended to increase the locus of control indicators, namely the indicator of belief in success, the confidence variable, namely the indicator of having weaknesses and fears, the need for achievement, namely the indicator of not liking paid work, the variable of innovation, which is an indicator of avoiding doing things.